REVIEW OF RESEARCH ISSUES OF DETERMINATION OF MECHANICAL PARAMETERS OF COMPOUND LOADING STRUCTURES AND WORKING BODIES - ABDUVAKHIDOV, MUTAKHKHIRKHON (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
There is a big use as carrying elements in technology and worker organ’s component design of technology. In article is organized review of the questions of the using and determinations mechanical parameters of component design, applicable as worker organ cotton picking machine and cotton bud picking machine, unripe cotton bell cleaner.